A Compact, Versatile Six-Port Radar Module for Industrial and Medical Applications. (12th December 2013) - Linz, Sarah; Vinci, Gabor; Mann, Sebastian; Lindner, Stefan; Barbon, Francesco; Weigel, R.; Koelpin, Alexander
Abstract : The Six-port receiver has been intensively investigated in the last decade to be implemented as an alternative radar architecture. Plenty of current scientific publications demonstrate the effectiveness and versatility of the Six-port radar for special industrial, automotive, and medical applications, ranging from accurate contactless vibration analysis, through automotive radar calibration, to remote breath and heartbeat monitoring. Its highlights, such as excellent phase discrimination, trivial signal processing, low circuit complexity, and cost, have lately drawn the attention of companies working with radar technology. A joint project involving the University of Erlangen-Nuremberg and InnoSenT GmbH (Innovative Sensor Technology) led to the development of a highly accurate, compact, and versatile Six-port radar module aiming at a reliable high-integration of all subcomponents such as antenna, Six-port front-end, baseband circuitry, and digital signal processing in one single package. Innovative aspects in the RF front-end design as well as in the integration strategy are hereby presented, together with a system overview and measurement results.